Inflammatory Potential of Four Different Phases of Calcium Pyrophosphate Relies on NF-κB Activation and MAPK Pathways - Campillo-Gimenez, Laure; Renaudin, Félix; Jalabert, Maud; Gras, Pierre; Gosset, Marjolaine; Rey, Christian; Sarda, Stéphanie; Collet, Corinne; Cohen-Solal, Martine; Combes, Christèle; Lioté, Frédéric; Ea, Hang-Korng (Frontiers in Immunology, 2018)
Background: Calcium pyrophosphate (CPP) microcrystal deposition is associated with wide clinical phenotypes, including acute and chronic arthritis, that are interleukin 1β (IL-1β)-driven. Two CPP microcrystals, namely monoclinic and triclinic CPP dihydrates (m- and t-CPPD), have been identified in human tissues in different proportions according to clinical features. m-CPP tetrahydrate beta (m-CPPTβ) and amorphous CPP (a-CPP) phases are considered as m- and t-CPPD crystal precursors in vitro. Objectives: We aimed to decipher the inflammatory properties of the three CPP crystals and one CPP phse and the intracellular pathways involved. Methods: Synthesized CPP phases and monosodium urate (MSU) crystals were used in vitro to stimulate the human monocytic THP-1 cell line or bone marrow-derived macrophages (BMDM) isolated from WT or NLRP3 KO mice. The gene expression of pro- and anti-inflammatory cytokines was evaluated by RT-qPCR; IL-1β, IL-6 and IL-8 production by ELISA; and mitogen-activated protein kinase (MAPK) activation by immunoblot analysis. NF-κB activation was determined in THP-1 cells containing a reporter plasmid. In vivo, the CPP inflammatory potential was assessed with the murine air pouch model via cell analysis and production of IL-1β and CXCL1 in the exudate. The role of NF-κB was determined by a pharmacological approach, both in vivo and in vitro. Results: In vitro, IL-1β production induced by m-CPPD, t-CPPD and m-CPPTβ crystals was NLRP3 dependent. m-CPPD crystals were the most inflammatory by inducing a faster and higher production and gene expression of IL-1β, IL-6, and IL-8 than t-CPPD, m-CPPTβ and MSU crystals. The a-CPP phase did not show an inflammatory property. Accordingly, m-CPPD crystals led to stronger activation of NF-κB, p38, ERK1/2 and JNK)MAPKs. Inhibition of NF-κB completely abrogated IL-1β and IL-8 synthesis and secretion induced by all CPP crystals. Also, inhibition of JNK and ERK1/2 MAPKs decreased both IL-1β secretion and NF-κB activation induced by CPP crystals. In vivo, IL-1β and CXCL1 production and neutrophil infiltration induced by m-CPPD crystals were greatly decreased by NF-κB inhibitor treatment. Conclusion: Our results suggest that the inflammatory potential of different CPP crystals relies on their ability to activate the MAPK-dependent NF-κB pathway. Studies are ongoing to investigate the underlying mechanisms.